Pemaknaan Semboyan Keraton Matan-Tanjung Pura: Potret Simbol Agama di antara Tradisi Mitos dan Logos - Andry Fitriyanto (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2023)
Mustike Indah Jaya Sempurna Dilupakan Pantang Dilangkah Tulah is a motto of the kingdom Matan-Tanjungpura, West Kalimantan. This sentence has a sacred value for the community. From a philosophical view, the motto is a symbol that has a specific meaning behind it. It is present as a cultural and religious symbol. The absence of an authoritative interpretation of this motto means that anyone can interpret it according to their capacity. The phenomenon of various tendencies in patterns of meaning is the main focus of this paper. This study uses a qualitative approach with a type of field research that is strengthened by an analysis of scientific literature. Data collection was carried out through observation, interviews, and documentation. This study resulted in several important points. First, the motto is identified as a cultural symbol that contains religious aspects as the basis of social norms or the philosophy of life of the people. Second, in the denotative aspect, the motto reflects aspects of art, mystery, preciousness, strength, luxury, beauty, and height, to the completeness contained in its vocabulary. Third, there is a tendency for connotative-normative meanings to view the motto as a social norm with all its recommendations and prohibitions, connotative-magical meanings to view the motto as a scientific symbol that is magical or supernatural in nature, and connotative-logical meanings to interpret the motto rationally. using historical literature. Fourth, there is a kind of shift in meaning between the elders who tend to interpret it mystically, and the younger generation who try to achieve objectivity in their interpretation. It is influenced by several factors, including age, knowledge, education, social status, and others.